PERAN KOMISI YUDISIAL DALAM PENGAWASAN PELANGGARAN KODE ETIK DAN PEDOMAN PERILAKU HAKIM - Umi Laili (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
The State of Indonesia is a democratic constitutional state, based on Pancasila and the1945 Constitution of the Republic State of Indonesia, which upholds human rights and guarantees all citizens at the same time in law and government and is obliged to uphold such law and government without exception.The judge is the organs of the court on which should be placed duty and great responsibility for law and justice can be enforced, but on the other hand Judge is also an ordinary man who in carrying out his duty that can’t be separated from mistakes either intentionally or unintentionally.Many public scrutiny that saw the duties of a judge was questioned, ranging from the behavior of a dormant judge while performing his duties in the courtroom, to the alleged bribery to the judge when handling a case including Judge's infidelity into a bleak portrait of public concern.Given the many phenomena of irregularities committed by Judges above, it is necessary an independent institution in charge of providing oversight of violations of ethical   codes   and   judicial   behavior  guidelines.  This   judicial   commission  was established to fulfill a sense of justice and truth for the community with a background.In  this  research,  the  author  uses  normative  legal  research  methods,  and empirical law research methods as well. However, researchers will focus more on normative legal research, while empirical law research serves as supporting information. Using primary legal materials, secondary legal materials, and tertiary legal materials.The oversight of the judicial commission is carried out both internally and externally to ensure that all judges as the principal implementers of the court function shall be of high integrity, honesty and professionalism, thereby gaining the trust of the community and seekers of justice.The public may participate in supervising the behavior of judges in order to bring about a clean and professional judiciary through community reports. Reports may be  conducted  by  individuals,  groups  of  people,  public  entities,  legal  entities, corporation or Non-Governmental Organizations (NGOs) who are aware of alleged code violations Judicial conduct ethics and judicial guidelines and not limited to the injured party. As reported is the Judge allegedly violating the Code of Ethics and Judicial Conduct Guidelines.